ANALYSIS OF THE IMPLEMENTATION OF LAW NUMBER 08 OF 1999 CONCERNING CONSUMER LEGAL PROTECTION AGAINST THE USE OF UNREGISTERED COSMETIC PRODUCTS FROM THE PERSPECTIVE OF ISLAMIC LAW (Study At Balai Besar Pengawas Obat Dan Makanan Bandar Lampung) - Diah Prayogi Diah; Ruslan Abdul Ghofur; Liky Faizal (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
The lack of supervision from the authorities coupled with the lack of public knowledge in differentiating genuine and counterfeit products has made the circulation of counterfeit cosmetics increasingly rampant in the market. The problems that occurred at BPOM Bandar Lampung, especially in supervision, found that many consumers bought cosmetic products that did not have quality, and there were no BPOM products. The purpose of this study was to determine the implementation of Law Number 8 of 1999 concerning consumer legal protection and consumer legal protection according to Islamic law at BPOM Bandar Lampung. This research is a qualitative research and is descriptive in nature. The results of field research show that consumer legal protection against the use of cosmetic products that are not registered at the Bandar Lampung Drug and Food Control Center is more focused on Article 4 which states that consumers have the right to comfort, security and safety in consuming goods and/or services. From the point of view of Islamic law, the distribution of cosmetic products containing harmful additives and without clear information is strictly prohibited by Islamic law. Giving explanations and information that is not true, mixing good things with bad things, showing examples of good things and hiding what is not good is included in fraud. This fraud has a detrimental effect on the buyer, and that is tyranny